(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
ABSTRACT The head of the environment as an extension of the hand of the Government in the area of the smallest of the Wards have a strategic role in order to provide service to the community while bridging the implementation of Government programs and activities, therefore in carrying out the duties and functions of the head of the environment required for professionals. Professionalism is measured from the ability to perform the duties and functions of a high quality, the right time, and with the procedures that are easy to understand. Of the approach, the concept of professionalism can be seen from the indicator: creativity (creativity), innovation (innovation) and Responsiveness (responsivity). This research was compiled based on qualitative research methods with data collection techniques in the form of observation, interview, documentation and technical analysis data used in this study is the analysis of qualitative data with the informant that add up to 48 people. The results showed that most heads of Environment in Lembeh South yet professional in carrying out the tasks and functions seen from less creative head of environment in providing services, as well as lack of innovation or new work being done in utilizing the technology. The factors that affect it, such as the level of education is still low, leadership, understanding of the tasks and functions, compensation, and yet the existence of measurable performance evaluation. Therefore need to be laid out an activity of coaching and training for the head of the environment in order to better understand the tasks and functions as well as increasing competence. Keywords: Professionalism, Head Of Environment